Sharia Business Ethics and Its Relevance to Umrah Service Standards in Indonesia - Rara Genta Munggarani Basri Rara; Syarifah Gustiawati Mukri; Muhamad Fatihul Ihsan (JURNAL ILMU SYARIAH, 2026)
This study analyzes the relevance of Sharia business ethics to umrah service standards in Indonesia and its integration in improving service quality. The approach is qualitative, using library research methods, drawing on the Qur'an, Hadith, academic literature, and government regulations. The analysis was carried out in a descriptive-analytical method using content analysis (content analysis). The results showed that the principles of amanah, siddiq, tabligh, and fathanah are very relevant to the standard of umrah services. Amanah ensures fund management and the certainty of departure; Siddiq ensures transparency in costs and facilities; Tabligh supports the communication and education of pilgrims; and Fathanah improves service professionalism. The integration of these principles strengthens formal regulation and establishes a conceptual model of fair, transparent, and quality service. The main challenges include profit orientation, price competition, and moral hazard risk. The implementation of Sharia ethics is key to improving PPIU's professionalism, protecting worshipers, and maintaining the blessings of worship.